Efektivitas Penggunaan Media YouTube dalam Pembelajaran Sistem Hybrid - Ariza, Hidra (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
The Covid-19 has an impact on accelerating the transformation of education in Indonesia. Starting from active online learning then developing into the implementation of hybrid learning. At this time, hybrid learning has become important to use due to the demands of developments in information and communication technology in all aspects of life, including in the world of education. The development of technology and information in the world of education has encouraged the emergence of innovative learning models which are useful as alternatives for solving the obstacles faced in traditional learning models. This hybrid learning system is seen as being able to support the concept of Independent Learning, Independent Campus. The use of a hybrid learning system at the tertiary level is a form of digital transformation in the world of higher education. Digital literacy is applied at the tertiary level in conjunction with the learning process using the hybrid learning method. One platform that can be used as a learning medium in this hybrid learning system is YouTube. YouTube was chosen as a learning medium because YouTube is easy to access and students can access learning materials on YouTube wherever and whenever they need. This research was conducted to see the effectiveness of using YouTube media in Hybrid system learning in the History of Islamic Education course. The results of the research that has been carried out is, YouTube media is effectively used as a learning medium for Islamic education history courses, this is proven by the result analysis that 74,33%. This means that most of the respondents agreed that YouTube media was effective in learning.